RESPOSTA FISIOLÓGICA DE Salvinia biloba Raddi (Salviniaceae) EXPOSTA À HIDROQUINONA - ROCHA, Carina Machado; SANTIAGO, Etenaldo Felipe; ARRUDA, Gilberto José; SANTOS, Jaqueline Silva (ANAIS DO ENIC, 2023)
-